PENERAPAN TRANSTHEORICAL MODEL BEHAVIORAL CHANGE TERHADAP KEPATUHAN BEROBAT PADA PASIEN MULTIDRUG RESISTANT TUBERCULOSIS DI PUSKESMAS KOTA DAN KABUPATEN JAYAPURA - Sulistiyani, Sulistiyani; Situmeang, Lamria; Aji, Rustam; Swastika, I Ketut (Media Penelitian dan Pengembangan Kesehatan, 2023)
Multi Drug Resistant Tuberculosis (MDR-TB) is still a global health problem. Indonesia is the 3rd country with an average of 5% cases per 100,000 population. For the Papua region, MDR-TB is still a major problem because the treatment success rate has not reached the WHO indicator (68.7%). The treatment of MDR-TB is complex and time-consuming, making patients non-compliant. Reports of low patient visits have made it possible to develop a promotive service program based on applying the Transtheoretical Model (TTM) of Behavioral Change. The TTM Model focuses on changing behavior with the main component of self-efficacy. The study aimed to determine the characteristics of patients, treatment compliance of MDR-TB patients, analyze the effect of applying the TTM behavioral change model with the level of treatment compliance of MDR-TB patients. The research method used a pre-experiment design with a one-group pre-test-post-test design. The study population was 35 patients at the city and district health centers of Jayapura. The instruments used were the Self-Efficacy For Appropriate Medication Use Scale (SEAMS) and TB Medication Adherence Scale (TBMAS). The effect test used a paired sample t-test with significance level p-value=0.05. This indicates an effect of changes in compliance behavior after being given health promotion by applying the Transtheoretical Model. Substantially, the level of adherence to taking medication in MDR-TB patients is also influenced by belief and motivation to recover. There is support from nurses at the puskesmas who often provide behavior change promotions, so patients have the strength and support of a good system that has a positive impact on increasing thoughts to achieve recovery. The importance of Increasing health promotion based on behavior change in MDR-TB patients can increase self-efficacy to recover so that it has an impact on adherence to taking medication.